Efficacy of Islamic-Integrated Cognitive Behavioral Therapy for Reducing Fear of Missing Out (FOMO) in Madrasah Students - Fuadi, Ikhsan; Casmini, Casmini (International Journal of Islamic Educational Psychology, 2026)
Fear of Missing Out (FOMO) has become an emerging psychological problem among adolescents due to intensive social media use, particularly among madrasah students. Excessive social media engagement may trigger anxiety, social comparison, emotional distress, and decreased academic concentration. This study aimed to examine the efficacy of Islamic-integrated Cognitive Behavioral Therapy (CBT) in reducing FOMO by incorporating Islamic values of gratitude (shukr), contentment (qana’ah), and trust in God (tawakkal) into cognitive restructuring and behavioral change processes. The study employed a quantitative approach using a true experimental pretest–posttest control group design. Participants consisted of Muslim senior high school adolescents (N = 20) with high FOMO levels who were assigned to experimental and control groups. Data were collected using the Online Fear of Missing Out Scale (ON-FOMO) and analyzed using Paired Samples t-Tests and Independent Samples t-Tests. The findings revealed a statistically significant reduction in FOMO scores among students in the experimental group (p = 0.001 < 0.05), with the mean score decreasing from 71.4 at pretest to 58.5 at posttest. Significant posttest differences were also found between the experimental and control groups (p = 0.001 < 0.05). Furthermore, the effect size (Cohen’s d = 2.48) indicated a very large intervention effect. These findings suggest that Islamic-integrated CBT is efficacious in reducing FOMO while strengthening students’ psychological and spiritual well-being in the digital era.